PENGARUH DISIPLIN KERJA, GAYA KEPEMIMPINAN DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN UMUM LEMBAGA PENYELENGGARA PELAYANAN NAVIGASI PENERBANGAN INDONESIA CABANG PALEMBANG - Rayendra Bambang Hirawan (Universitas Bina Taruna Gorontalo, 2023)
This study aims to determine the effect of work discipline, leadership style, and work experience on employee performance. The method used is a description with a quantitative approach. The sample in this study were 80 people. LPPNPI Indonesia is a state-owned company engaged in air navigation services. Airnav was established on September 13, 2012 through Government Regulation No. 77 of 2012. The establishment of Airnav Indonesia was based on two facts about Indonesia's aviation conditions, namely, PT. Angkasa Pura I, PT. Angkasa Pura II, and the Airport Technical Implementation Unit which concurrently has the task of managing the airport land sector and flight navigation. As well as recommendations from ICAO for specialized agencies or institutions in the field of navigation to establish aviation. The results of this study indicate that work discipline has a significant effect on employee performance, leadership style has no effect on employee performance and work experience has an effect on employee performance.